Materia e valore. La metafisica dell’immaginazione di Gaston Bachelard e l’esempio de La nausée - Adinolfi, Ciro (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
Thanks to his philosophy of imagination, Gaston Bachelard opens spaces of deep and original reflection on the relationship between subject and object. Moving his theoretical axis on the matter, which is different than to the object, Bachelard shows the emergence of the rêveur, who is improperly comparable to the subject. This happens because the rêveur, through his rêverie, rather than owning the object in the cognitive act, valorises his personal experience with the contribution of the oneiric dimension, which arises by means of matter’s inner forces. Consequently, Bachelard’s metaphysics leads us to reread the relationship between the individual and the being, towards a valorisation of the being. The purpose of this article is to rethink those reflections, in the light of the theme of value. Bachelard’s criticism of La nausée is an example of the application of this metaphysics. Keywords: Bachelard, Imagination, Matter, Sartre, Value. Keywords: Bachelard, Imagination, Matter, Sartre, Value.